Democratic Republic of Timor-Leste : 2022 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2022)
Timor-Leste has made impressive strides in economic development and institution building. Yet, it is a low-income and fragile country with pressing development needs. A large fraction of the population faces chronic food insecurity, and significant gaps exist in health, education, and infrastructure. With active oil fields nearly depleted, little progress has been made in diversification while fiscal sustainability is at high risk. Higher food and oil prices are fueling higher inflation, exacerbated by political spending pressures ahead of the general elections in 2023.